PSYCHOLOGICAL CONFLICT OF THE MAIN CHARACTER IN PAUL GREENGRASS’ MOVIE “CAPTAIN PHILLIPS” - Anggraeni, Rezki Amelia; Weda, Sukardi; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
Psychological conflict is a condition that we often encounter in our daily lives. It isalso known as interpersonal conflict and is defined as a conflict caused by the characteritself. Commonly, it arises when people make difficult decisions. According to Kurt Lewin’s theory, psychological conflicts are divided into three types: (1) approach-approach conflict (an individual presented with two desirable alternatives), (2) avoidance-avoidance conflict (an individual presented with two undesirable alternatives), and (3) approach-avoidance conflict (an individual presented with twochoices, desirable and undesirable alternatives at the same time). In literary work,a character is a person who has a conflict, and then they are taking action to solve the problem that happens. Every problem must also have an impact that can affect life, particularly on ourselves, both mentally and physically. That’s why the researcher carrying out this research is to analyze what kinds of psychological conflicts were experienced by Capt. Richard Phillips and how these psychological conflicts impact his mental state. This research method is descriptive and qualitative with a focus on Kurt Lewin`s theory. This research data is taken from Captain Phillips’s movie. Other data were collected from various references, namely journals, thesis, articles, and online sources. Data analysis techniques include data reduction, data display, and conclusion drawing (Miles and Huberman, 1994). In this study, based on the actions, feelings, and utterances of the main character, the researcher found 29 data with the dominant psychological conflict being avoidance-avoidance conflict. The impact of the psychological conflict experienced by Captain Richard Phillips as the main character is mental stress and poor physical health.